AB0767 The association of ferritin autoantibodies with takayasu arteritis. (23rd January 2014) - Große, K.; Moosig, F.; Schmidt, R.E.; Witte, T.; Baerlecken, N.T.
Abstract : Background: Takayasu arteritis (TA) may be difficult to diagnose since diagnostic biomarkers have not been established so far. In a previous study, we could show the presence of autoantibodies against the human ferritin heavy chain protein (HFC) in sera of patients with giant cell arteritis (GCA) and/or polymyalgia rheumatica (PMR) (1). Objectives: To study the prevalence of autoantibodies against HFC in TA. Methods: We established 7 ELISAs for the detection of autoantibodies against HFC. As autoantigen we used the full recombinant HFC expressed by E. coli or one of six different peptides of the HFC: 1-18Aa (purity 98.8%), 19-45Aa (purity 98.8%), 52-78Aa purity 98.3%), 79-104Aa (purity 98.8%), 105-143Aa (purity 98.4%), 145-183Aa (purity 98.5%). We collected sera of 51 patients with TA, 49 sera of fever patients with underlying chronic infectious and malignant diseases, which are known for having unspecific autoantibodies, and 100 blood donors' sera served as controls. Results: The best results were obtained by using ferritin pedtides as antigens. By combining different ELISAs detecting autoantibodies against HFC peptide 19-44A, 79-104A and 105-144A, we were able to detect ferritin peptide antibodies in 31/51 (61%) TA patients. For early TA, the frequency was lower than in early GCA and PMR (previous study up to 92%). In the controls, 0/100 (0%) of the blood donors were positive and 11/49 (22%) of the fever patients were positive. Conclusions: Considering the lack of biomarkers for TA, autoantibodies against peptides of HFC could be helpful as a marker for TA. References: Baerlecken NT, Linnemann A, Gross WL, Moosig F, Vazquez-Rodriguez TR, Gonzalez-Gay MA, Martin J, Kötter I, Henes JC, Melchers I, Vaith P, Schmidt RE, Witte T. Association of ferritin autoantibodies with giant cell arteritis/polymyalgia rheumatica. Ann Rheum Dis. 2012 Jan 5. [Epub ahead of print] Disclosure of Interest: None Declared